AI Tools for Personalized English Learning: Bridging the Gap Between Technology and Language Acquisition - Abdullah Kafabih; Morista Sasi Apriliana; Nanda Ardianing Putri; Eko Wardoyo; Siki Tyas Retnani; Rozanah Katrina Herda; Sheikha Majid (Wahana Pendidikan, 2026)
Language learning has become increasingly effective with the support of artificial intelligence, particularly in English language learning contexts. This study aims to explore how English as a Foreign Language learners utilize artificial intelligence to support personalized learning and to examine their perceptions of this technology. The study employed an explanatory sequential mixed methods design, beginning with quantitative data collection followed by qualitative exploration. Quantitative data were collected through a structured questionnaire involving 200 undergraduate learners from the English Education Department of a public university in Indonesia, while qualitative data were obtained through semi structured interviews with 10 selected participants. Quantitative data were analyzed using descriptive statistics and qualitative data were examined through thematic analysis. The findings indicate that artificial intelligence features such as real time feedback, adaptive content, voice recognition, and gamified tasks contribute to improvements in learners’ writing, reading, speaking, and listening skills. In addition, artificial intelligence provides interactive and accessible learning support that allows learners to engage flexibly in personalized learning. However, limitations related to meaningful interaction and contextual understanding remain challenges when artificial intelligence is not used judiciously.